Anatomic-pathologic and taphonomic case study Lestodon Gervais, 1855 São Paulo State and deposited at the Museu Nacional/UFRJ collection - Cabral, Uiara Gomes; Henriques, Deise Dias Rêgo (Anuário do Instituto de Geociências, 2007)
Abstract